Dispersal duration mediates selection on offspring size. Issue 4 (21st October 2016) - Svanfeldt, Karin; Monro, Keyne; Marshall, Dustin J.
Abstract : Offspring size varies at all levels of organisation, among species, mothers and clutches. This variation is thought to be the result of a tradeoff between offspring quality and quantity, where larger offspring perform better but are more costly to produce. Local environmental conditions alter the benefits of increased offspring size and thereby mediate selection on this trait. For sessile organisms, dispersal is a crucial part of the offspring phase, and in animals, bigger offspring tend to better endure longer dispersal distances than smaller offspring because they have more energy. Theory predicts that increasing distances between suitable habitats strengthens selection for larger offspring. We manipulated the dispersal duration of offspring of different sizes in the bryozoan Watersipora subtorquata and then examined the relationship between offspring size and post‐metamorphic performance in the field. We found that selection on offspring size is altered by larval experience. Larger offspring had higher post‐settlement performance if the larval period was short but, contrary to current theory, performed worse when the larval period was extended. The reversal of the relationship between offspring size and performance by extending the larval phase in Watersipora may be due to the way in which offspring size affects growth in this species. Regardless of the mechanism, it appears that experiences in one life‐history stage alter selection on offspring size in another stage, even when they occupy identical habitats as adults.